Innovative Policy of Regional Development of Industry - Natalia Petrenko (Науковий вісник Мукачівського державного університету. Серія Економіка, 2018)
The mechanism for regulating the activities of industrial enterprises can be imagined as an integrated system of forms, methods, means, through which the state's influence on industrial policy is carried out. Regional industrial policy is part of the state and is determined by the competitive environment, the direction of socio-economic development, resource potential, the size of the budget, etc. Formation and implementation of industrial policy at the regional level are closely interconnected with the issues of effective development of industries that make up the industry in the region. The main element for regional industrial policy at the present stage of economic reform is investment policy, as the most important component of the formation of sustainable development. However, sustainable development of the region is directly related to the processes, what is happening in the country and in the world and, of course, should take into account these processes. Therefore, these processes should be investigated at the level of the country and region, in particular the chemical industry, as one of the promising branches of industry. The article analyzes the processes of development and implementation of innovation policy of regional development of industry on the example of Cherkasy region. It is revealed that in Ukraine there are many obstacles for innovative activity that have different degrees of influence on the development of industry, in particular the chemical complex, connected with the lack of necessary legislative, political, economic, moral and other tools for regulating this process. The factors contributing to conducting an active innovation policy in the chemical industry are highlighted. It has been established that the attracted funds of various financial structures, budget funds, investors and enterprises funds are gaining importance in the implementation of innovation industrial policy. It is summarized that the most important direction of development of the chemical complex in the near future should be innovation development, and the most important factor in the development of innovation environment should be considered state policy in the direction of development and implementation of innovations that takes into account the current world investment processes and trends, international norms and rules